Morphology and Postnatal Development of Lower Hindlimbs in Desmodus rotundus (Chiroptera: Phyllostomidae): A Comparative Study - Reyes Amaya, Nicolás Rafael (2017)
The hindlimbs in bats are functionally adapted to serve as a hook to attach to the mother from birth, and to roost during independent life. Although bats exhibit different terrestrial locomotion capabilities involving hindlimbs, hindlimb morphology and postnatal development have been poorly studied. We describe in detail the postnatal development and bone morphology of hindlimbs of the nimble walker vampire bat, Desmodus rotundus, and compare adult characters with the insectivorous Molossus molossus (erratic walker) and the frugivorous Artibeus lituratus (non-walker). The advanced ossification of most hindlimb elements of D. rotundus at the newborn stage is consistent with the functional role of this structure at birth in bats. The development completion events of hindlimb bone elements and bone processes in D. rotundus coincide with the cranial bone processes completion and suture closure events. Those events occur when individuals begin to feed by themselves. There are differences in the number and position of bone processes and sesamoids in adults among the compared species, most of which are described for the first time, and in the case of D. rotundus and M. molossus mostly related to a greater and tight articulation between elements. These facts seem to be closely associated with the different terrestrial locomotion capabilities, and in the case of the exclusively sanguivorous D. rotundus with specializations for obtaining food.